SUCCESSFUL THERAPEUTIC MANAGEMENT OF CANINE TRANSMISSIBLE VENEREAL TUMOUR IN NATIVE BREED DOGS OF TAMIL NADU - J, ARUNPANDIAN; B, NEETHU; N, SRIVASTAVA; KUJUR, ANJU; G, ASWINISIVAN (The Indian Journal of Animal Reproduction, 2021)
Canine transmissible venereal tumour (TVT) is a tumour of genital tract commonly occurring in dogs and foxes.Stray dogs act as reservoir for TVT. Incidence of TVT is higher in developing nations like India because of higherpopulation density of stray dogs as well as due to lack of proper veterinary care in villages. The present paper placeson record successful management of TVT, one in a male Chippiparai and other one in female Rajapalayam dogsbelonging to Rajapalayam village of Tamil Naduwith chemotherapy using a plant alkaloid, Vincristine Sulphate atweekly intervals for 3 weeks. Both the animals recovered uneventfully.
Keywords: Transmissible Venereal Tumour (TVT); Plant alkaloid; Vincristine Sulphate; Rajapalayam; Chippiparai; Genital tract